MANAGEMENT OF DIGITAL-BASED MARKETING STRATEGY IN INCREASING THE QUANTITY OF UMRAH PILGRIMS OF PT ARUDAM 99 PROBOLINGGO BRANCH - Zainur Ridho; Muhammad Jalaluddin Assayuthy (Fakultas Syariah dan Ekonomi Islam Universitas Ibrahimy, 2025)
The purpose of this research is to examine the digital marketing strategies used by PT. Arudam 99 Cabang Probolinggo to increase the quantity of umrah participants. The approach used in this research methodology is descriptive qualitative, with the title